Provider experiences with the large-scale 'Helping Babies Breathe' training programme in Tanzania. (2nd January 2018) - Isangula, Kahabi Ganka; Kassick, Megan E.; Kairuki, Allan Kaijunga; Meda, Robson Amunga; Thomas, Erica; Temu, Akwila; Msemo, Georgina; Azayo, Mary; Nelson, Brett D.
Abstract: Objectives: Worldwide, there has been renewed emphasis on reducing neonatal mortality in low-resource countries. The Helping Babies Breathe (HBB) programme has been shown to reduce newborn deaths. The aim of this study is to present provider-level perceptions and experiences of the HBB programme implemented at-scale in Tanzania and identify key lessons learned for scalability in similar and other settings. Methods: Focus group discussions with HBB-trained providers were conducted using a prospective longitudinal study design between October 2013 and May 2015. A semi-structured discussion guide was used to facilitate the focus groups which were held 4–6 weeks and 4–6 months post-HBB training. Data were managed using NVivo software and analysed thematically. Results: A total of 222 focus group discussions were conducted in 252 trained facilities and involved 599 providers across 15 regions of Tanzania. Birth attendants reported that the training programme helped increase knowledge, skills and confidence, and that the provided equipment simplified resuscitation. Supportive supervision and regular follow-up visits were considered critical for skills retention. On the other hand, the brief 1-day training in Tanzania, small financal incentives, intra-facility rotations of trained attendants, staff shortages, limited rescucitation spaces and mastery of the bag-and-mask were considered challenges to the HBB programme in Tanzania. Discussion: The HBB programme was largely very well received during its first at-scale implementation in Tanzania. Addressing the main challenges cited by participants, particularly the training duration, may increase provider satisfaction with the HBB training programme.